When you and your customers make the products together - Powell, Juliette, 1976- (FT Press Delivers, 2010)
"This Element is an excerpt from 33 Million People in the Room: How to Create, Influence, and Run a Successful Business with Social Networking (ISBN: 9780137154357) by Juliette Powell. How to dramatically improve your products' performance by building them around user ideas and submissions"--Resource description page.